Quercetin attenuates cisplatin-induced fat loss - Lin, Yi-Chin; Chen, Li-wen; Chen, Yun-Chu; Chan, Shu-Ting; Liao, Jiunn-Wang; Yeh, Shu-Lan (European journal of nutrition, 2021)
Purpose The major aim of the present study was to determine the effects of quercetin, a well-known flavonoid, on attenuating cisplatin (CDDP)-induced fat loss and the possible mechanisms. Methods Tumor-bearing nude mice and tumor-free BALB/c mice were administrated with CDDP alone or in combination with quercetin by a diet containing 0.1% or 1% quercetin (LQ or HQ) or by intraperitoneal injection (IQ) to determine the effects of quercetin on the anticancer effect of CDDP or CDDP-induced fat loss. The effects of quercetin on fat accumulation in CDDP-exposed 3T3-L1 cells were also determined. Results We first showed that HQ and IQ significantly enhanced the anticancer effect of CDDP by upregulating p53- and p21-associated pathways, while tended to attenuate CDDP-induced fat loss in tumor-bearing nude mice. The study in 3T3-L1 cells showed that CDDP decreased the fat accumulation accompanied by strong upregulation of the expression of six genes which are associated with fat metabolism, while quercetin completely suppressed such an effect. The tumor-free BALB/c mice study consistently showed a protective effect of HQ on CDDP-induced body weight and epididymal fat loss. HQ also increased the fat levels in liver and muscle tissues. In epididymal fat tissues, HQ consistently attenuated CDDP-induced changes in fat metabolism-associated gene expression. However, CDDP alone or in combination with HQ did not affect the food intake. Conclusions This study demonstrates that quercetin possesses the potential to suppress CDDP-induced fat loss may partly through the regulation of the fat metabolism-associated gene expression.